Validation of data collected with mobile metabolic measurement systems over time during active commuting - Rosdahl, H.; Salier-Eriksson, J.; Schantz, P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: With the aim of attaining valid descriptions of metabolic demands during active commuting in greater Stockholm new approaches have been used. We have previously reported evaluations of a mobile metabolic measurement system both in the laboratory (Rosdahl et al. 2010) and during simulated field conditions, including check of stability over time (Salier-Eriksson et al. 2012). However, to be confident with the validity of the metabolic data collected over time during mobile field conditions we have used new approaches. Methods: During the period of data collection in the field with the mobile metabolic system (Oxycon Mobile, JLAB 5.21, CareFusion, Germany) this was controlled once by the manufacturer and 11 times in our own laboratory using a commercially available metabolic calibrator (Vacumed, syringe No.1750 and mass flow controller No. 17052, Ventura, CA, USA). On each occasion VO2 and VCO2 were checked between 1 - 4 L/min with the corresponding VE at 40-160 L/minute and tidal volume at 2 L. The calibration information (offset, gain and delay time) from the O2 and CO2 analyzers and volume sensor, being collected pre and post the field commuting tests, was analyzed. Additionally, the results of each experiment was critically examined in several means including an inspection of parallelism in heart rate and VO2. Results and Discussion: As examined with the metabolic calibrator, all parameters (VO2, VCO2, RER and VE) measured by the mobile metabolic system were in general well within the boundaries of acceptance. Adequate stability of the O2 and CO2 analyzers and volume sensors for the time duration of each experiment was confirmed by small differences in the pre- and postcalibration factors. Based on two researchers´ ocular inspections of heart rate and oxygen uptake recordings during active commuting, all but one were rated as generally parallel, and thus passed this type of check of the field measurements. Overall, the present investigation favors that data collected over time with a mobile metabolic system can be validated by a combination of metabolic calibrator measurements, analyses of calibration information and a critical examination of the variables from each single measurement.